The Effect of Land Planning on CO2 Carbon Production and Their Effect on Gross Regional Domestic Products (GRDP) Riau Province - Rita Rita (Green Publisher Indonesia, 2022)
This study aims to analyze the effect of land clearing on CO2 carbon production due to forest fires that often occur in Riau Province in 2018-2019, and to analyze the opportunities for forest fires to occur in Riau Province using available data. The results of the logistic regression show that forest fires are more likely to occur in peaty forests even though in reality the soil is not peaty in Riau. Land clearing causes the emission of carbon dioxide (CO2) gas into the atmosphere, including the conversion of forests to small-scale agriculture. The aim of the study was to measure CO2 emissions from an economic perspective due to land clearing for plantations by regional domestic product companies (GRDP), such as rubber plantations (Hevea brasiliensis) aged 8-10 years, oil palm (Elaeis guineensis Jacq) plantations aged 5-6 years. , and ginger (Zingiber officinale) aged 0-6 months. The conversion of HRG was originally intended to obtain economic benefits in the form of an increase in the gross regional domestic product (GRDP) of the plantation sector. However, these efforts have also led to the loss of the benefits of HRG environmental services. This paper is intended to provide an overview of the economic value of the lost environmental services as a result of the conversion and degradation of HRG Riau and its impact on sustainable development and to consider the potential for restoration as an effort towards sustainable economic development. The results showed that CO2 from the opening had a contribution to increase the concentration of CO2 in the atmosphere. Carbon control from small-scale agriculture on peatlands makes an important contribution to achieving the target for reducing greenhouse gas emissions from the agricultural sector.